2006
DOI: 10.1002/ejoc.200500981
|View full text |Cite
|
Sign up to set email alerts
|

N‐Carboxymethylated 6,7‐Dimethoxy‐4‐trifluoromethylcarbostyrils as Fluorescence Markers for Amino Acids, Peptides, Amino Carbohydrates and Amino Polysaccharides

Abstract: The highly fluorescent 6,7-dimethoxy-3-trifluoromethylcarbostyril 2 was regioselectively carboxymethylated with bromoacetates 4 at N-1 to give esters of type 5 in good yield. After saponification to 8, succinimidoyl (OSu) esters 9 were prepared. Dyestuffs 9 were reacted in slightly basic aqueous media under mild conditions with free amino acids, esters and peptides to give the fluorescently labeled amino acid derivatives 11 and 13 in good yields. Similarly, aminoglucose

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
20
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 46 publications
3
20
0
1
Order By: Relevance
“…Only the absorption of the CN-substituted building block 17 is significantly shifted to longer wavelengths. The data obtained for building blocks 16 and 17 agree well with the ones reported for the pure dyes by Uray, Stadlbauer, and coworkers [15] [16]. Since these dyes are intended to be used as fluorescence donors, their fluorescence properties are important.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…Only the absorption of the CN-substituted building block 17 is significantly shifted to longer wavelengths. The data obtained for building blocks 16 and 17 agree well with the ones reported for the pure dyes by Uray, Stadlbauer, and coworkers [15] [16]. Since these dyes are intended to be used as fluorescence donors, their fluorescence properties are important.…”
supporting
confidence: 83%
“…-Recently, Uray, Stadlbauer, and co-workers published their efforts on improving the photophysical properties of carbostyrils by a systematic investigation of substituent effects which converged in a push-pull model with two electron-donating groups at position 6 and 7 and an electron-withdrawing group at the 4-position. Their first attempts culminated in compound 4 carrying a CF 3 group at C(4) [15]. Alkylation at N(1) had no influence on the photophysical properties, and derivatives of 4 showed an absorption maximum l max at 359 -361 nm in H 2 O and extinction coefficients around 10 000.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Table 1 are excitation maxima listed which are for all alkylated species almost equal. We also found that there is no significant difference to the Nlinked 6,7-dimethoxycarbostyrils described earlier [5]. Interestingly, extinction coefficients are about 10-30% larger comparing N1-derivatives with the new O6-isomers varying between 9000 and 13000 in DMSO and 10000-16000 in water [5].…”
Section: -13supporting
confidence: 61%
“…[186,215] Zusätzlich zur weiteren Verbesserung der Verfahren für die Synthese von Seltenerd-dotierten b-NaYF 4 -Nanopartikeln mit engen Partikelgrößenverteilungen, passenden optischen Eigenschaften und Partikelgrößen sowie einer verbesserten Anwender- In den letzten fünf Jahren wurde der Nutzen von UCNPs in Nukleinsäure-und Immunassays für In-vivo und In-vitroVerfahren beschrieben, allerdings sind die Anwendungen bisher vielfach auf das simple Einbringen von lumineszierenden Nanopartikeln in biologische Systeme und den Nachweis der Partikel selbst beschränkt. Um molekulare Fluoreszenzmarker (Molekulargewicht um 300 g mol À1 ) [452] mit der Möglichkeit der Positionsbestimmung von Zellstrukturen im Nanometerbereich zu ersetzen, sind Partikel mit einer Größe von 20 nm oft zu groß. Die Gesamtqualität der derzeitigen UCNPs ist für das anspruchsvollste Feld der Bildgebung in der Biomedizin -die selektive Darstellung von molekularen und zellulären Geschehnissen in der molekularen Neurobildgebung -bei weitem nicht ausreichend.…”
Section: Weitere Anwendungenunclassified